Correlation analysis of hemoglobin, albumin, lymphocyte, platelet score and platelet to albumin ratio and prognosis in patients with lung adenosquamous carcinoma - Zhang, Tiantian; Liu, Wei; Xu, Chunhua (Frontiers in Oncology, 2023)
Objective To investigate the effect of hemoglobin, albumin, lymphocytes, platelet (HALP) score and platelet to albumin ratio (PAR) on prognosis of patients with lung adenosquamous carcinoma (ASC) after surgery. Patients and methods A total of 52 patients diagnosed with ASC after surgical resection were collected from Nanjing Chest Hospital from 2012 to 2021, and their general clinical data, pathological data and laboratory indexes were collected. The changes of Alb and Plt levels before and after surgery, HALP scores (hemoglobin albumin lymphocytes/platelets), and postoperative PAR, PLR, NLR were retrospectively analyzed, and their influence on the prognosis of patients with ASC was investigated. The cut-off value of △Alb, △Plt, postoperative PAR, PLR and NLR were determined by the receiver operating characteristic (ROC) curve, the optimal cut-off value of HALP score before and after surgery was calculated by using X-tile software, and the clinicopathological characteristics were compared between the high PAR and low PAR groups and between high HALP score and low HALP score group to analyze the factors influencing the prognosis of patients with ASC. Univariate and multivariate Cox proportional regression analyses were used to assess independent risk factors affecting overall survival (OS) and disease-free survival (DFS) in patients with ASC. Kaplan-Meier method was used to evaluate the correlation between OS, DFS and PAR and HALP score. Results A critical value of PAR was 7.40×10^9 and an area under the curve (AUC) of 0.737 (95%CI: 0.597-0.876, P = 0.004). The best cut-off value of the preoperative HALP score was 24.3. Univariate Cox analysis showed that the cut margin (P = 0.013), the degree of differentiation (P = 0.021), N stage (P = 0.049), △Plt (P = 0.010), △Alb (P = 0.016), PAR (P = 0.003), NLR (P = 0.025), PLR (P = 0.029), preoperative HALP score (P = 0.000) and post-operative HALP score (P = 0.010) were all associated with postoperative OS in ASC patients. Cut margin (P = 0.029), the degree of differentiation (P = 0.045), maximum tumor diameter (P = 0.018), N stage (P = 0.035), △Plt (P = 0.007), △Alb (P = 0.007), PAR (P = 0.004), NLR (P = 0.041), PLR (P = 0.030), preoperative HALP score (P = 0.000), and postoperative HALP score (P = 0.011) were related to postoperative DFS in ASC patients. Multivariate analysis revealed that PAR (HR: 6.877, 95%CI: 1.817-26.038, P = 0.005), differentiation degree (HR: 0.059, 95%CI: 0.006-0.591, P = 0.016) and preoperative HALP score (HR: 0.224, 95%CI: 0.068-0.733, P = 0.013) had significant effect on OS. Tumor maximum diameter (HR: 3.442, 95%CI: 1.148-10.318, P = 0.027) and preoperative HALP score (HR: 0.268, 95%CI: 0.085-0.847, P = 0.025) had significant influence on DFS. Conclusion PAR and preoperative HALP score were potentially useful biomarkers for evaluating the outcome of patients with postoperative ASC. PAR, the degree of differentiation and preoperative HALP score were independent prognostic factors for postoperative OS in ASC patients. Maximum tumor diameter and preoperative HALP score were independent prognostic factors for postoperative DFS in ASC patients.